Pendidikan Mitigasi Bencana Gempa Bumi untuk Kepala Sekolah : Upaya Meningkatkan Kesadaran dan Aksi - Keumala Citra Sarina Zein, Meillyta, Widya Soviana, Cut Nawalul Azka, Wahyuni (Bansigom Na Publisher, 2024)
Education regarding earthquake disaster mitigation has a very vital role in daily life, especially in Indonesia which often experiences earthquake phenomena as part of the Pacific Ring of Fire. Earthquake preparedness and risk reduction is not only the responsibility of the government, but also the responsibility of the community. Education on safe behavior during an earthquake and active participation in emergency response plans can play a role in reducing the impact of disasters. Therefore, Community Service (PKM) activities need to be carried out with the aim of, among other things, providing education and increasing awareness of the school community regarding earthquake facts. This is expected to increase awareness about disaster risks and how to deal with them. Training, equipping school principals, as well as carrying out earthquake disaster simulations and evaluating these activities are concrete steps in achieving this goal. The conclusion of the Community Service activities related to the theme of earthquake disaster mitigation education for school principals is an effort to increase public awareness of the risks and procedures for dealing with earthquake disasters.